Clinical and genetic characteristics in a central-southern Chinese cohort of early-onset Alzheimer's disease - Liang, Zhihou; Wu, Yan; Li, Chuanzhou; Liu, Zhijun (Frontiers in Neurology, 2023)
Background Mutations in the presenilin-1 (PSEN1), presenilin-2 (PSEN2), and amyloid precursor protein (APP) genes have been commonly identified in early-onset Alzheimer's disease (EOAD). Some of the mutations in the three causative genes, especially the PSEN1 gene, result in variable phenotypes and exhibit clinical heterogeneity among EOAD families. Methods Using next-generation sequencing (NGS), we performed genetic screening in a Chinese cohort of 18 patients with EOAD, consisting of five familial EOAD and 13 sporadic cases. Results We identified two likely pathogenic PSEN1 mutations (one novel) and a novel APP mutation in three cases of EOAD, where two are familial and one is sporadic, respectively. In addition, we detected a few variants of uncertain significance (VUS) in several genes, including not only the two known variants in PSEN2 (p.H169N and p.V214L) but also genes causal of other types of dementia or previously identified as risk factors for AD, suggesting the possible involvement of multiple genes in the etiopathology of AD. The patients carrying PSEN1 mutations had an earlier mean age at the onset than those with PSEN2 or APP variants. The initial symptoms varied greatly among patients in the EOAD cohort, from progressive memory impairment and epilepsy to uncommon motor symptoms such as involuntary tremors in the upper extremities. Conclusions In conclusion, our study provides further evidence of the genetic profile of patients with EOAD from China and expands the mutation spectrum of both PSEN1 and APP. In addition, our results highlight the clinical heterogeneity in patients with EOAD and mutations in PSEN1, PSEN2, and APP and suggest strong effects of genetic variants on clinical phenotypes. Future functional studies are needed to clarify the interaction between AD-causative gene mutations and phenotypic heterogeneity.